A soft‐sphere‐imbedded pseudo‐hard‐particle model for simulation of discharge flow of brick particles. Issue 10 (5th May 2016) - Gui, Nan; Yang, Xingtuan; Jiang, Shengyao; Tu, Jiyuan
Abstract : A novel hybrid approach of soft‐sphere‐imbedded pseudo‐hard‐particle model is proposed to cope with the complex collision of nonspherical particles. In this approach, the boundary of a host hard particle is covered by a series of soft‐spheres, which are allowed to oscillate about the equilibrium position according to the position, orientation, and shape configuration of the host particle. The collision processes are twofold: as a predictive process, particle‐particle interaction takes place through the collision between the distributed soft‐spheres, which causes subspheres to deviate from the equilibrium positions; as a corrective process, relaxation is superposed to allow the soft‐spheres to move back toward the equilibrium positions quickly. Consequentially, this process generates the force and torque on the host particle and determines its movement. Finally, after validation, this new model is used to explore the effects of aspect ratio and base angle on the discharge of brick particles in hoppers. © 2016 American Institute of Chemical Engineers AIChE J, 62: 3562–3574, 2016